2014
DOI: 10.1111/ijpp.12134
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacy asthma service achieves a change in patient responses from increased awareness to taking responsibility for their asthma

Abstract: A sustained experience/multiple visits in a service may lead to more concrete changes in patient perceptions of severity, beliefs, health behaviours and enhanced self-efficacy and control. The study highlights a need for such asthma services in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Recent studies demonstrated that pharmaceutical care services improve drug adherence and health outcomes by focusing on inhalation technique and patient education [11e24]. This may also lead to enhanced disease awareness, changes in patients' beliefs and attitudes towards treatment and improved self-efficacy and control [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that pharmaceutical care services improve drug adherence and health outcomes by focusing on inhalation technique and patient education [11e24]. This may also lead to enhanced disease awareness, changes in patients' beliefs and attitudes towards treatment and improved self-efficacy and control [25].…”
Section: Introductionmentioning
confidence: 99%
“…Further to that, a literacy-sensitive, culturally and linguistically appropriate approach should also be incorporated [69][70][71][72][73]. Despite the fact that correct inhaler technique can be taught within 2 and 8 min (depending on the device), the health care practitioner may need to invest additional time with the patient over time, providing sustained experience/multiple visits to change patient's perceptions of their asthma severity, beliefs, health behavior, and enhanced self-efficacy [74]. As part of this process, perhaps tools like the In-CheckDial, Inhalation Manager, Aerosol Inhalation Monitor (AIM) [52,53], which are often used to evaluate patients' breathing maneuvers as they relate to the use of different inhalers, could be used to engage patients around their inhaler technique.…”
mentioning
confidence: 99%
“…Our survey showed high physician acceptance of pharmacists' monitoring of therapy, an approach associated with increased drug adherence. [23,24] Physicians also strongly endorsed pharmacists' prescribing a holding chamber, medications to treat minor conditions and smoking cessation aids; this is supported by the proven benefit of pharmacists' interventions in asthma care on inhaler technique, quality of life and asthma control, [9,25,26] renewing or extending of the ICS prescription as well as adjusting its form and posology were also highly accepted. Recognising that a key reason for suboptimal ICS use is the insufficient number of renewals authorised by physicians, [27,28] pharmacists' renewal of asthma controller drugs has the potential to increase the use of maintenance ICS.…”
Section: Discussionmentioning
confidence: 99%